Artificial intelligence in islamic education: Ethics and its implications for islamic education - Fouad Larhzizer; Dedy Irawan; Arif Usman; Aprizon; Ibrahim Hammad; Riky Supratama; Siti Qomala Khayati; Eka Mahargiani Rokhma; Alfian Eko Rochmawan; Edi Susanto (Yayasan Azhar Amanaa Yogyakarta, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to the world of education, including Islamic education. This study aims to analyze the ethics of AI usage and its implications for Islamic education from the perspective of sharia values and the objectives of Islamic law (maqāṣid al-sharī‘ah). Using a library research approach, data were collected from academic literature, scientific articles, and relevant documents discussing AI, Islamic ethics, and education. The findings indicate that Islam conditionally supports technological advancement, including AI, as long as it aligns with key ethical principles such as justice, trustworthiness (amānah), responsibility, transparency, and privacy protection. AI is considered capable of enhancing the quality of religious learning through personalized content, automated instruction, and expanded access to education, particularly in remote areas. However, AI also poses a number of ethical challenges, including the potential distortion of religious understanding, the dehumanization of the teacher's role, algorithmic bias, and violations of moral and spiritual values. Therefore, a clear Islamic ethical framework is essential, along with the active involvement of scholars (‘ulamā’), increased digital literacy among educators, and the development of authentic Islamic content. With these foundations, AI can serve as a tool to support the holistic and ethical vision of Islamic education without compromising its core divine values.